Quantum Mechanics - Reed, B. Cameron ([S.l.] : Jones & Bartlett Learning, 2007)
Quantum Mechanics and its applications are a vibrant, central part of today$1 (Bs research in both experimental and theoretical physics. Designed for the one-semester course, Quantum Mechanics expertly guides students through rigorous course material, providing comprehensive explanations, accessible examples, and intuitive equations. This text$1 (Bs in-depth coverage of essential topics, such as harmonic oscillator, barrier penetration, and hydrogen atoms, skillfully bridges the gap between sophomore introduction texts and lower-level graduate treatments. Students will find this user-friendly text, with numerous examples and applications, sets a solid foundation for future courses in the area of Quantum Mechanis
Keywords: Quantum Mechanics